2021
DOI: 10.1038/s41418-021-00824-w
|View full text |Cite
|
Sign up to set email alerts
|

TCF3 is epigenetically silenced by EZH2 and DNMT3B and functions as a tumor suppressor in endometrial cancer

Abstract: Endometrial cancer (EC) is the most common gynecological malignancy worldwide. However, the molecular mechanisms underlying EC progression are still largely unknown, and chemotherapeutic options for EC patients are currently very limited. In this study, we found that histone methyltransferase EZH2 and DNA methyltransferase DNMT3B were upregulated in EC samples from patients, and promoted EC cell proliferation as evidenced by assays of cell viability, cell cycle, colony formation. Mechanistically, we found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 30 publications
(27 reference statements)
0
21
0
Order By: Relevance
“…Furthermore, there are few reports on DNMT3B in cancer. However, studies have previously reported that DNMT3B was an oncogene that played a crucial role in the progression of various types of cancer, including endometrial cancer (EC) ( Gui et al, 2021 ), lung cancer ( Yang et al, 2014 ), and PCa( Agarwal et al, 2013 ), and conversely DNMT3B has implicated as a TSG in lymphoma ( Hlady et al, 2012 ).…”
Section: The Functional Role Of Various Types Dnmts In Cancermentioning
confidence: 99%
“…Furthermore, there are few reports on DNMT3B in cancer. However, studies have previously reported that DNMT3B was an oncogene that played a crucial role in the progression of various types of cancer, including endometrial cancer (EC) ( Gui et al, 2021 ), lung cancer ( Yang et al, 2014 ), and PCa( Agarwal et al, 2013 ), and conversely DNMT3B has implicated as a TSG in lymphoma ( Hlady et al, 2012 ).…”
Section: The Functional Role Of Various Types Dnmts In Cancermentioning
confidence: 99%
“…Cell proliferation was determined by a BrdU Cell Proliferation ELISA Kit according to a previous study [ 38 ]. In addition, colony formation assay was also performed to evaluate glioblastoma cells proliferation [ 39 , 40 ]. Briefly, glioblastoma cells were seeded into 6-well plates and cultured for 14 days, which were then fixed in methanol for 30 min, stained with 0.5% crystal violet at room temperature for 15 min and carefully rinsed with tap water.…”
Section: Methodsmentioning
confidence: 99%
“…DNMT1 and DNMT3B expression in cancerous lung tissue is correlated with gene promoter hypermethylation at multiple TSG promoters, including FHIT and p16 INK4a ( 155 ). A recent study found that in endometrial cancer, concurrent DNMT3B and EZH2 upregulation in cancer cells results in the epigenetic silencing of TCF3 ( 156 ). TCF3 is a transcriptional activator of CCKN1A (p21 WAF1/Cip1 ), and its silencing results in accelerated endometrial cancer cell proliferation ( 156 ).…”
Section: Dnmt Gene Expression Changes In Cancermentioning
confidence: 99%
“…A recent study found that in endometrial cancer, concurrent DNMT3B and EZH2 upregulation in cancer cells results in the epigenetic silencing of TCF3 ( 156 ). TCF3 is a transcriptional activator of CCKN1A (p21 WAF1/Cip1 ), and its silencing results in accelerated endometrial cancer cell proliferation ( 156 ).…”
Section: Dnmt Gene Expression Changes In Cancermentioning
confidence: 99%